Pengantar Studi Madrasah Hadis - Mutaqin, Rizal Samsul; Solihin, Firman (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2022)
The position and function of hadith which is very vital in Islamic teachings has become a driving factor for hadith experts to continue to maintain and maintain hadith from generation to generation. This care and maintenance began in the time of friends, and has never stopped until now. It was the friends and tābi'īn who initially spread to various regions carrying the mission of spreading hadith by organizing scientific circles (halaqah) in these areas. In its development, in these areas—which were fronted mainly by different companions—then a hadith study community was formed, each of which had its own characteristics, which were influenced by regional conditions and brought influence in the field of hadith to the area. These communities are called by contemporary hadith researchers the “Madrasah Hadith.” This paper aims to discuss “Madrasah Hadith,” starting from the definition, urgency, and technical steps of the study, as a reference for researchers who are interested in conducting this study. This research is a type of qualitative research using historical methods. The approach used is descriptive-analytic with data collection techniques usinglibrary research. The results of this study indicate that the Hadith Madrasa is a